Extended Salvage Pelvic Lymph Node Dissection in Patients with Recurrent Prostate Cancer - Daniar K. Osmonov; Alexey V. Aksenov; Annkathrin Boller; Almut Kalz; Diana Heimann; Isa Janssen; Klaus-Peter Jünemann (Advances in Urology)
Background. Treatment of patients with a biochemical recurrence (BCR) of prostate cancer (PCa) is generally difficult and without valid treatment options. Since 2004 we have been developing therapeutic possibilities for these patients. Methods. We retrospectively analyzed a cohort of 41 patients with a BCR of PCa and a mean followup of 40.3±20.8 months. Group 1 (n=10): salvage radical prostatectomy (sRP) with SePLND (salvage extended pelvic lymph nodes dissection) (initial treatment: combined brachytherapy). Group 2 (n=22): SePLND (initial treatment: radical prostatectomy (RP)). Group 3 (n=9): SePLND (initial treatment: RP and adjuvant radiation therapy (RT)). We observed PSA, PSA-velocity, localization of LNs and LNs+, BCR-free period, and BR (biochemical response). Results. Group 1: 60% with BCR-freedom (mean 27.2 months). Group 2: 63.6% with BCR-freedom (mean 17.5 months). Group 3: 33.3% with BCR-freedom (mean 17.6 months). In total, BCR-freedom was observed in 23 of 41 patients (56.1%) after salvage surgery. 75.6% of all patients showed a BR. 765 LNs were removed and 14.8% of these were LN+. Conclusions. The BCR-free period and BR are comparable in all three groups. Sensibility to ADT can be reestablished and prolonged as a result of SePLND. Multicenter studies are needed for a reliable output.